Design and experiment of a direct‐drive wave energy converter using outer‐PM linear tubular generator. Issue 3 (30th January 2017) - Huang, Lei; Hu, Minqiang; Yu, Haitao; Liu, Chunyuan; Chen, Zhongxian
Abstract : Research on direct‐drive wave energy converter linear generators has mostly focused on synchronous inner permanent magnet (PM) linear generators. In this study, an outer‐PM tubular linear generator is designed to increase the power density and distance of relative movement. The motion equations of heaving buoys are derived on the basis of hydrodynamic theory. Two buoys are designed in accordance with the real wave condition in the Yellow Sea in China. The design process of the proposed generator is elucidated. Considering cogging force and voltage, the authors optimise the linear generator and determine the final parameters. The generator performance is evaluated using the finite element method. The integrated wave energy converter system consists of a linear generator, inner buoys, outer buoys, an electricity post‐processor, and a communication component. The system is manufactured and placed in the Yellow Sea based on the design results. The measured voltage is highly consistent with the simulation data. All results show that the system is well suited for wave energy conversion.